PENGARUH LIVE STREAMING DAN KONTEN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN E-COMMERCE SHOPEE - Fadillah, Elfani; Indah.S, Desshita; Ramdani, Fahad (REUGREUG: Jurnal Bisnis Digital, Akuntansi, Kewirausahaan, dan Manajemen, 2026)
This study aims to analyze the effect of live streaming and promotional content on consumers’ purchase decisions on the Shopee e-commerce platform, both partially and simultaneously. The method used is a quantitative approach with an associative research design. The research population includes all Shopee consumers who have watched the live streaming feature and viewed promotional content, with a sample size of 100 respondents selected through purposive sampling. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS software.The results show that, partially, the live streaming variable has a positive and significant effect on purchase decisions. Likewise, the promotional content variable is also found to have a positive and significant effect on purchase decisions on a partial basis. Simultaneously, the test results prove that live streaming and promotional content have a positive and significant effect on consumers’ purchase decisions. The Adjusted R Square value of 0.720 indicates that these two variables are able to explain 72% of the variation in purchase decisions, while the remaining percentage is influenced by other factors outside this research model. These findings emphasize the importance of real-time interaction and the quality of digital content in marketing strategies to influence shopping behavior in the digital era.